South Korea and Chinese Conflict over THAAD: How it started and the way it ended - Anggraining Tias (UIN ALAUDDIN MAKASSAR, 2020)
After North Korea’s fourth nuclear tested in January 2016, U.S. and South Korea has an official discussion started in early February 2016. The choice to deploy the anti-missile defense system THAAD was made in July 2016 and therefore the first launchers in May 2017. This launch was in line with the tenure of President Moon Jae In at that point. President Moon Jae In initially opposed THAAD but has now accelerated its deployment in response to North Korea’s nuclear test on September 3. Even before the official THAAD discussion started, Beijing expressed its opposition to the system. Although China is additionally against North Korea’s nuclear development, THAAD is seen as an arrange to undermine China’s strategic interests within the region. And because of this, China giving a ‘punishment’ to South Korea. This research aims to describe how the conflict between South Korea and Chinese can happen, the impact of the place THAAD in South Korea to the relations between two countries, and the way the conflict ended. This research uses neorealism as an approach. The methodology employing a qualitative method and collecting the data employing Historical-comparative research.